Pursue or shoot? Effects of exercise-induced fatigue on the transition from running to rifle shooting in a pursuit task - Nibbeling, N.; Oudejans, R. R. D.; Cañal-Bruland, R.; van der Wurff, P.; Daanen, H. A. M. (Ergonomics, 2013)
To investigate to what degree exercise-induced fatigue influences behavioural choices, participants' transition from running to rifle shooting in a pursue-and-shoot task was assessed. Participants ran on a treadmill and chased a target in a virtual environment and were free to choose when to stop the treadmill and shoot at the target. Fatigue increased progressively throughout the 20-minute test. Results indicated that shooting accuracy was not affected by fatigue. However, the distance to the target at which participants decided to shoot showed a U-shaped relationship with fatigue, R² = 0.884, p = 0.013. At low fatigue levels (ratings of perceived exertion [RPE] < 6.5), the distance to the target at which participants shot decreased, whereas at higher fatigue levels (RPE > 6.5) shooting distance increased again. At high levels of fatigue, participants stopped running sooner, aimed at the target longer and shot less often. Findings indicate that physiological parameters influence not only perception but also actual transitions between different actions.